Semióticas da(s) masculinidade(s) em um grupo de homensque exercem violência contra as mulheres - Claudia Natividade Felipe (2012)
In this study we analyzed the discourses based on the analytical framework of Social Semiotics and Multimodality of men who exercise violence against women. To this end, our tool to collect oral/visual data was three focus groups. Our aim was to analyze the participantsmeaning making process related to their personal experience with attention to the following items: a) their lexical choices to represent the world around them; b) the evaluations that they attribute to themselves, to others and, to things around themselves; c) the way they constructthese meanings, having in mind that the context of production is permeated by power and ideological positions. To investigate the representational system of the participants in question we based our study on Systemic Functional Grammar and, more specifically, on transitivity aiming to investigate the actions they denote themselves and other people, thus creating their relational experiences. To investigate the interpersonal system of the participants we based our research on the appraisal and, more precisely, on the attitudinal component, mapping their lexical choices regarding judgments, appreciations and affects. The semiotic Modes and Resources like gestures, postures and body movements were analyzed bearing in mind their affordances and how they coupled to the lexical choices producing several meanings.Thereby, from the paradigm of multimodality was possible to investigate how meaning was produced through various semiotic Modes and Resources. The meaning making process was discursively analyzed according to proposals of critical readings related to the problem of violence against women, that is, under the paradigm of gender and masculinity(ies) studies.The data analysis showed the participants process of meaning making revealing their choices in group interactions, thus with different types of bound configurations and stance. The results show the production of a sign in which the participants identify, orient and represent themselves in their intimate relationships. Therefore, we analyze how such a sign is connected to the power relations established by gender dynamics and the social construction of masculinity(ies) to, later, to inquire how this sign relates to the context of violence in intimate relationships.